Typology of Malay Toponyms in Bengkalis (Jurnal Bahasa, 2025)
Toponymy is a field that examines place names, such as streets, villages, districts, cities, and states. The naming of places is typically associated with geographical or topographic features. This study focuses on place names found in Bengkalis, an island located in the Riau province. It aims to explore the resilience and continuity of the Malay language through the place names in Bengkalis. The toponymic analysis is conducted using linguistic typology, which classifies languages based on structural features found in place names. Data were collected using extensive methods, including the use of maps and fieldwork, by photographing and recording the names of shops, streets, mosques, and villages in both urban and rural areas of Bengkalis. The photography was guided by coordinates obtained from Google Maps. Findings show that the place names in Bengkalis are characterized by agglutinative language features, including single-word forms (Pusara, Bhakti), complex forms (Mekar Jaya, Harian Makmur), derivatives (Al-Muslihin, Desa Penebal), and compound words (Jl. Putra Jaya, Desa Sukamaju). Some mosque names are in Arabic, whereas names of streets, alleys, and shops tend to use Malay names, alongside Javanese and Chinese. This suggests that the Malay language is predominantly used in place naming, serving as an indicator of Malay identity in Bengkalis.Keywords: Toponymy, Bengkalis, typology, agglutinative, Malay, identityFull text: PDF